Real-Time High Jump Wearable Device with ESP8266 for High-Performance and Low-Injury - Roslan, Muhammad Faris; Ahmad, Afandi; Amira, Abbes (International Journal of Integrated Engineering, 2018)
In the world of sports, the injury is unavoidable, however, the performance is the first priority. The percentage of the athletes to get injured is very high due to the fallibility of athlete jumping themselves. Therefore, this study presents the design and implementation of high-performance and low-injury real-time high jump wearable device by using ESP8266 microcontroller. The proposed wearable device is built because of there is no device to monitor this sport during training. There are three (3) parts have been integrated to build this wearable device – input, process and output. The input consists of global positioning system (GPS) sensor that attached to the waist and force sensing resistor (FSR) sensor was placed at the bottom of the ankle as a wireless input for data captured. These data were then being processed by ESP8266 microcontroller hardware device with an embedded wireless fidelity (Wi-Fi) module on the same chip that has been programmed and results obtained were displayed via the mobile app. Graphical user interface (GUI) of the wearable device has been designed using C language code using OpenHAB software and data from the wearable device were also available in log formats. The outcomes obtained have shown encouraging results since all data can be visualised and monitored in real-time, history of the training can be retrieved and the benchmark data acts as a guide to the other athlete to improve the performance.